Identifikasi Morfologi Dicranoweisia cirrata, Hypnum cupressiforme, dan Trichostonum brachydontium Di Kawasan Hutan Kota Serang, Banten - Rifqiawati, Ika; Ramadhani, Insanti Camelia; Nurjanah, Lilis Siti; Khodijah, Titi Ida (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2024)
Moss is a low-level species that is abundant. This typical group of green land plants is one of the plants that has a habitat in humid places, lives in groups, and is very easy to find around the environment. One of the moss distribution areas is in the Serang City Forest area, Banten. The purpose of this study was to identify the morphological characteristics of Moss Plants (Bryophyta) in the Serang City Forest area, Banten. In addition, to explore more varieties of moss species in the Serang City forest area, Banten. The research was conducted in October 2022 using the exploration method. Several types of moss that we get based on research results, including Dicranoweisia cirrata, Hypnum cupressiforme, and Trichostonum brachydontium Brunch. The benefits of this research are as a source of information related to the diversity and morphology of mosses in the Serang City Forest area, Banten.